Dukungan Arab Saudi Terhadap Pemerintahan Ali Abdullah Saleh Dalam Revolusi Rakyat Yaman - Tristiana, Veny; Muharjono, Muharjono (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
Generally we know that countries in the Middle East is a country that still adheres monarchy and many dictator who dominate for decates. For example is Saudi Arabia, Jordania, Yemen and many else. However, after the emergence of jasmine revolutions occurred in the Middle East in 2011, it was make all changed. Started with the collapse success of dictatorial regime in Tunisia, Libya and other Middle East countries and one of them is Yemen. Yemen as a country located in the Middle East, borders with Saudi Arabia in north is also affected by the jasmine revolution. The people of Yemen nally managed to bring down the regime of Ali Abdullah Saleh who have led Yemen for 32 years at the beginning of January 2011. The revolution that occurred in Yemen would also have an impact on the political stability of other countries are neighborhood.